2015
DOI: 10.3892/ijmm.2015.2368
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS-based metabolomic analysis of human papillary thyroid carcinoma tissue

Abstract: Papillary thyroid carcinoma (PTC) is the most common type of thyroid cancer. Elucidating the molecular network that is altered in PTC may lead to the identification of the critical insight into the pathogenesis of PTC. Thus far, little is known regarding the global metabolomic alterations of PTC. Gas chromatography coupled with mass spectrometry-based metabolomics was used to analyze metabolomic alterations in matched PTC and normal thyroid tissues obtained from the patients. Multivariate statistical analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Moreover, enhancement of G6PD activity during cell cycle progression, in particular S/G2 phases, was also reported in the human colon cancer cell line HT29 (38). Upregulation of G6PD levels was described in papillary thyroid carcinoma (PTC) (39) and renal cell cancer (40). On the other hand, a very weak G6PD activity was observed in lung cancer (33), and variable results were obtained in breast carcinoma cells (41, 42).…”
Section: Glucose-6-phosphate Dehydrogenasementioning
confidence: 99%
“…Moreover, enhancement of G6PD activity during cell cycle progression, in particular S/G2 phases, was also reported in the human colon cancer cell line HT29 (38). Upregulation of G6PD levels was described in papillary thyroid carcinoma (PTC) (39) and renal cell cancer (40). On the other hand, a very weak G6PD activity was observed in lung cancer (33), and variable results were obtained in breast carcinoma cells (41, 42).…”
Section: Glucose-6-phosphate Dehydrogenasementioning
confidence: 99%
“…Metabolomics has been extensively employed in cancer research, and plenty metabolic alterations are found in various types of cancers . Results from several recent works demonstrated that metabolomics techniques could help to discriminate different types of thyroid lesions for differential diagnosis, provide significant information about disease progression and unveil potential targets for therapy . However, most of the previous studies used tissue samples except one used serum, one used plasma and one used urine .…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of HIF-1 α has been also associated with distant metastasis in PTC [ 24 , 25 ]. Furthermore, HIF-1 α activates the expression of glycolytic enzymes such as the hexokinase II (HKII), phosphoglycerate kinase (PGK), glucose-6-phosphate dehydrogenase (G6PDH), and lactate dehydrogenase A (LDH-A), or glucose and lactate transporters, such as glucose transporter 1 (GLUT1) and the monocarboxylate transporter 4 (MCT4), that have been found overexpressed in TC [ 26 – 29 ]. Overall, these findings suggest that some cells within thyroid tumors rely on aerobic glycolysis for energy production, thus exhibiting the Warburg phenotype.…”
Section: Thyroid Cancer Metabolism: Warburg and “Reverse Warburg” mentioning
confidence: 99%
“…Lactate is also a potent signaling molecule involved in angiogenesis [ 74 , 75 ]. Interestingly, when compared with healthy tissues, TC shows increased expression levels and activation of LDH-A, the key enzyme of lactate production in cells [ 26 , 58 ].…”
Section: The Current Status Of Metabolomics In Tc Researchmentioning
confidence: 99%